EFEKTIVITAS MODEL PEMBELAJARAN TIPE GROUP TO GROUP EXCHANGE (GGE) TERHADAP HASIL BELAJAR MATEMATIKA - S, Reski Masyitoh (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The research with the background that student learning outcomes in mathematics are quite low because students feel bored with conventional learning models that are too monotonous. In fact, the demands of the curriculum aim to foster student activity while learning takes place. The research methodology uses a quasi-experimental approach with pre-test and post-test in both classes. The population of this study were all students of class VII at MTs Al-Manar Medan with a total of 60 people. Which divides bags VII-1 and VII-2. Data sampling technique with total sampling. Data analysis was carried out after giving the pre-test and post-test in both classes. This is based on the criteria for calculating the t-test, namely t_count = 8.57 and t_table = 2.998, because t_count t_table with 30 each sample. And in terms of effectiveness, it can be seen from the N-gain test with the results of the N-Gain calculation This shows that the experimental N-Gain value with moderate criteria is 90%. While showing that the N-Gain value of the control class with moderate criteria is 80%. So it can be concluded that the scores of students taught with the Group To Group Exchange (GGE) type learning model are higher than the scores of students taught with conventional learning models in class VII MTsN Al-Manar.Â